LEADERSHIP STYLE AND WORK MOTIVATION: DRIVING PERFORMANCE OF ISLAMIC BOARDING SCHOOL - Sari, Niki Puspita; Muhammad, Helmi; Aini, Nur (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2023)
This study analyzes the effect of transformational leadership and work motivation on performance of the administrators of the Nurul Hidayah Islamic Boarding School, Malang, East Java. This study uses a quantitative approach and data collection through questionnaires distributed to 33 boarding school administrators. The results of multiple linear regression analysis show that transformational leadership significantly affects the performance of the Nurul Hidayah Islamic Boarding School administrators. However, work motivation has no significant effect on the performance of the management. The results of this study provide positive implications for the leadership of Islamic boarding schools in improving the performance of the management through the implementation of transformational leadership values such as charisma, inspirational motivation, intellectual stimulation, and attention to individuals.